2017
DOI: 10.1038/s41598-017-12997-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of a Prediction Equation to Estimate Risk of Intraoperative Hypothermia in Patients Receiving General Anesthesia

Abstract: Inadvertent intraoperative hypothermia (core temperature <36 °C) is a frequent but preventable complication of general anesthesia. Accurate risk assessment of individual patients may help physicians identify patients at risk for hypothermia and apply preventive approaches, which include active intraoperative warming. This study aimed to develop and validate a risk-prediction model for intraoperative hypothermia. Two independent observational studies in China, the Beijing Regional Survey and the China National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…they reported that those with major-plus surgery, longer operation duration and>2 h, intravenous unarmed fluid infusion (>1000 ml) significantly are at risk of core hypothermia similar to study reported that those patients with elevated baseline core temperature prior to anesthesia) and high ambient temperature) are significantly lower at risk of core hypothermia 15 , we found there is a positive correlation between the operation duration and post-operative core temperature (r=0.056), but not significantly (p=0.429), possibly due to insufficient sub-sample size as those =>120 min operation duration were only 4 patients which is in agreement with another study 17 the patients with higher ASA physical status were more at risk of hypothermia 2 . In our study we could not find any significant correlation between post-operative hypothermia and different ASA physical status (p=0.404).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…they reported that those with major-plus surgery, longer operation duration and>2 h, intravenous unarmed fluid infusion (>1000 ml) significantly are at risk of core hypothermia similar to study reported that those patients with elevated baseline core temperature prior to anesthesia) and high ambient temperature) are significantly lower at risk of core hypothermia 15 , we found there is a positive correlation between the operation duration and post-operative core temperature (r=0.056), but not significantly (p=0.429), possibly due to insufficient sub-sample size as those =>120 min operation duration were only 4 patients which is in agreement with another study 17 the patients with higher ASA physical status were more at risk of hypothermia 2 . In our study we could not find any significant correlation between post-operative hypothermia and different ASA physical status (p=0.404).…”
Section: Discussionsupporting
confidence: 57%
“…The incidence of inadvertent post-operative hypothermia among a Kurdish sample in Iraq was 31.0% with mild severity only also showed a significant reduction in the overall post-operative core temperature, with both genders, and different age categories so lower compared to other studies reported 57.8% hypothermia in 185 adult patients underwent scheduled emergency non-cardiac surgery in ICU admission 13 , 44.8% hypothermia in operations of more than two hours 14 and 32% in another study 15 , study showed that male patients were more affected by hypothermia (34.3%) compared to females (27.7%) and adults (42.9%) compared to pediatric patients (27.2%). However, the overall differences of hypothermia between males and females (p=0.059) and between adult and pediatric patients (p=0.256) were not statistically significant.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have reported that the risk factors for intraoperative hypothermia are age, BMI, preoperative systolic blood pressure, heart rate, baseline core temperature, ASA-PS score, the type of anesthesia and surgery, the duration of preparation and surgery, and ambient temperature [ 20 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, previous studies did not include the PI as a risk factor for intraoperative hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are currently only two published prediction models for intraoperative hypothermia. Both have different approaches when compared to our models 26 , 37 . Kasai and colleagues developed a logistic model based on 400 cases and achieved a sensitivity of 81.5% and a specificity of 83% for intraoperative hypothermia.…”
Section: Discussionmentioning
confidence: 99%